When are individuals innovative?: Three-way interaction among openness to experience, innovative climate, and job complexity - Park, Ho Hwan; Zhou, Youjia; Choi, Myungweon (Journal of Personnel Psychology, 2018)
This study aims to explain: (a) what types of individuals are likely to exhibit innovative behavior and (b) when they are more likely to do so. For this purpose, the study uses trait activation theory (Tett & Burnett, 2003; Tett & Guterman, 2000) as a theoretical framework and simultaneously examines the characteristics of the individual performing the job (openness to experience), the context within which the job is performed (innovative climate), and the nature of the job (job complexity). An analysis of survey data collected in China suggests that innovative climate and job complexity have a joint moderating effect on the relationship between openness to experience and innovative behavior. Based on the results, implications for research and practice are discussed.
Keywords: Innovative behavior; Innovative climate; Job complexity; Openness to experience